Gerakan Sosial Masyarakat Eks Penghuni Lama Gusuran UIN Raden Fatah Kampus B Jakabaring - Nurfitriyanti, Nurfitriyanti; Adytyas, Nico Oktario (Ampera: A Research Journal on Politics and Islamic Civilization, 2022)
ABSTRAKSocial movements are increasingly believed to be tools of interest to realize social change when people are faced with social problems (problems). This research is motivated by the social movement of the former residents of the evicted former UIN Raden Fatah Jakabaring where the former community (five business) demand compensation rights for their land and buildings that have been evicted due to the land acquisition of Campus B UIN Raden Fatah in 2015. some people who have land rights and are proven by official certificates in accordance with statutory regulations demand their rights, namely compensation for land and buildings that have been evicted to the provincial government. South Sumatra and UIN Raden Fatah, after deliberation, the results did not find agreement, so the provincial government proposed to the community that the land acquisition case (eviction) was directed to the legal domain of the Palembang city court to find the best solution so that it could be resolved fairly so that no parties who feel aggrieved.The purpose of the study was to determine the dynamics of the ex-eviction community in the construction of the Raden Fatah Jakabaring UIN building and the form of the ex-community social movement towards the acquisition of eviction land at UIN Jakabaring. The research methodology used is a qualitative method. Narrative-descriptive research with an inductive-deductive approach from the truth of the case to the general public regarding a phenomenon that occurs. research instrument with interview sheets and documentation, data collection techniques through in-depth interviews with parties related to the land dispute case of UIN Raden Fatah.The results showed that the dynamics of the social movement of the former (five business) residents of the former evicted UIN Raden Fatah Jakabaring, namely the community worked hard to demand compensation for their land and buildings that had been evicted by submitting the case to the Palembang city court with the assistance of a resident's attorney. namely Herman Iskandar who was represented by Rozaillah et al. With this, the case was won by the former Panca Usaha community with the results of negotiations by Governor Herman Deru to the former community. So that the community is given two choices from the results of the negotiations, namely compensation in the form of an allocation by the governor of South Sumatra, the first choice is the allocation of vacant land in the Jakabaring area and the second option is flats in the Kertapati area. The form of the movement is a resistance movement